Hamartia, Amatia and Katastrophe: Semantics of Anagnorisis Around a Tragic-Political Langue - Arancibia-Carrizo, J (CENTRO ALTOS ESTUDIOS FILOSOFICOS & CIENCIAS SOCIALES-CENALTES, 2024)
This article examines the semantics of anagnorisis in the diegesis of Thucydides and the tragic poets. Linking the narrative corpus of Greek tragedy and of stasis in the democracy of Classical Greece, the text formulates two exercises: First, through the examination of some lexical items that constitute the semantic field of tragedy (hamartia, amatia and katastrophe), it is established a link between << tragic >> flaw >> and anagnorisis that occur to the tragic hero and the Athenian citizen narrated by Thucydides. Second, through the investigation of the lexemes enunciated in the anagnorisis of the tragic hero and the Athenian citizen, with the notion of << tragic syntagm >> , the article overlaps the semantic field of the tragic and historiographic diegesis to postulate the conjunction of a tragic-political langue in common.